Performance of a five-axis machine tool as a coordinate measuring machine (CMM) - Md Mizanur RAHMAN; Rene MAYER (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2016)
The use of machine tools for on-machine coordinate measurement on the workpiece is becoming commonplace. However, numerous errors can adversely affect the measurement accuracy. For instance, the inter-axis parameters are major contributors to the overall machine tool's inaccuracy hence estimation and compensation of such errors are prerequisite to fully exploit the machine's measurement capability. This paper presents a scheme to assess the accuracy of coordinate measurement by probing a precision sphere mounted on the machine table for different rotary axes indexations. Only the sphericity of the reference sphere is assumed and neither its size nor position. All individual probing data from all indexations are used for the assessment of the apparent out of sphericity of the reference sphere. Machine readings are processed either directly, using the machine nominal model, or using a compensated model. This provides a fast method to validate on-machine measurement before and after compensation with the exception of isotropic scale effects.